The Effect of Think Pair Share Cooperative Learning Model on Students’ Mathematical Communication Ability - Kevin Marito Sihombing; Mangaratua M. Simanjorang (Jurnal Pendidikan Matematika (JPM), 2025)
This study aims to determine the effect of the Project Based Learning (PjBL) model with the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach on students’ learning interest and mathematics learning outcomes in Grade VII at SMP Negeri 1 Pancur Batu. This research employed a quantitative approach using a quasi-experimental method with a pretest-posttest control group design. The sampling technique used was cluster sampling, with two classes selected as samples: Class VII-2 as the experimental class, which received treatment using the PjBL model with the STEAM approach, and Class VII-1 as the control class, which was taught using a conventional learning model. The instruments used were a learning interest questionnaire and a mathematics learning outcomes test. The data analysis using an independent sample t-test showed a significant difference between students’ learning interest and learning outcomes in the experimental and control classes. The t-test significance value for learning interest was 0.013 < 0.05, and for learning outcomes was 0.001 < 0.05. Thus, it can be concluded that the Project Based Learning model with the STEAM approach has a significant effect on improving learning interest and mathematics learning outcomes of Grade VII students.